Capacitação de profissionais da atenção primária à saúde para educação em Diabetes Mellitus - Torres, Heloisa de Carvalho; Amaral, Marta Araujo; Amorim, Maria Marta; Cyrino, Antonio de Pádua Pithon [UNESP]; Bodstein, Regina (Univ Fed São Paulo, Dept Enfermagen, 2010)
Objective: To present the proposal of educational workshops on diabetes and a strategy of evaluation aimed at upgrading the professionals' performance in primary care. Methods: The workshops were implemented using participatory methodology, play techniques, experiences, and group dynamics, involving the participation of 85 health professionals from Units of Primary Care, in the city of Belo Horizonte, MG. The knowledge about the disease and the skills required for self-care were measured by applying specific instruments. The workshops were evaluated based on the instrument: developed for that purpose. Results: There were limitations in the knowledge of professionals about pathophysiology and the disease's complementary tests. The workshops helped to awaken the potential of professionals (reflection, criticism and creativity) necessary to change the educational process. It was considered a pedagogical strategy, easy to understand, interactive and playful. Conclusions: The workshops contributed to the planning of the educational process and the structuring of an evaluation model of practices of health and education promotion in diabetes.
Training of professionals, acting in primary health care, in Diabetes Mellitus education
Capacitación, de profesionales que actúan en la atención primaria a la salud, en educación em Diabetes Mellitus
Keywords: Human resources formation; Health education; Primary health care; Diabetes Mellitus